2017
DOI: 10.1038/s41598-017-12044-9
|View full text |Cite
|
Sign up to set email alerts
|

Using a Novel Microfabricated Model of the Alveolar-Capillary Barrier to Investigate the Effect of Matrix Structure on Atelectrauma

Abstract: The alveolar-capillary barrier is composed of epithelial and endothelial cells interacting across a fibrous extracelluar matrix (ECM). Although remodeling of the ECM occurs during several lung disorders, it is not known how fiber structure and mechanics influences cell injury during cyclic airway reopening as occurs during mechanical ventilation (atelectrauma). We have developed a novel in vitro platform that mimics the micro/nano-scale architecture of the alveolar microenvironment and have used this system to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 46 publications
(53 reference statements)
3
52
0
Order By: Relevance
“…As a result, it was found that the stiffness of hybrid matrices significantly affects the barrier function of the epithelium/endothelium. An increase in the rigidity or density of the matrix led to a change in the structure of the cytoskeleton and a change in cell permeability [178]. Reprinted from [173] with permission from Nature Publishing Group, © 2017.…”
Section: Hybrid Biomaterials Applied For Lungsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it was found that the stiffness of hybrid matrices significantly affects the barrier function of the epithelium/endothelium. An increase in the rigidity or density of the matrix led to a change in the structure of the cytoskeleton and a change in cell permeability [178]. Reprinted from [173] with permission from Nature Publishing Group, © 2017.…”
Section: Hybrid Biomaterials Applied For Lungsmentioning
confidence: 99%
“…Adherence of NCI-H292 cells; tuning mechanical properties of materials [177,178,248] bFGF and AA2P based PGA/PLA Improving cells adhesion and stimulates cells proliferation and differentiation [249] Kidney (Section 6.2) Mg(OH) 2 and acellular ECM PLGA Neutralization of the effects induced by degradation of PLGA products, suppression of inflammatory reactions [186] l-DOPA and collagen IV PCL Improving cells adhesion and proliferation [250] Liver (Section 6.3) ECM-molecules PLA Microenvironment manipulation; changes of gene expression, protein contents, and cell adherence [251] PCL [252] HGF based Gelatin Controlled release for enhancement of the in vivo therapeutic effects RGD and YIGSR based PCL and PLA Improved hepatocyte adhesion [196] Cardiac muscles (Section 7.1) bFGF based PLGA Neovascular formation [253] Laminin based PU Improving cells adhesion [254] Skeletal muscles (Section 7.2)…”
Section: Gelatin Based Pcl Pgamentioning
confidence: 99%
“…An in vitro model of atelectrauma was used as previously described. (28,78) Briefly, polyacrylamide gels containing 10% w/w acrylamide (Bio-Rad) and 0.25% w/w bisacrylamide (Bio-Rad) were fabricated on 40 mm glass slides (20 kPa, 200 µm thickness).…”
Section: In Vitro Atelectrauma Modelmentioning
confidence: 99%
“…Matrix proteins such as collagens, elastin, laminin, fibronectin, and glycosaminoglycans (GAGs) are preserved through the decellularization process, but there are reports of up to a 50% loss of most of these components compared to native ECM [32,33]. Variations in ECM composition and stiffness can have a profound effect on cell phenotype, as well as cell attachment and barrier function [34][35][36]. High collagen and fibronectin content promote cell attachment at the expense of suboptimal barriers, indicative of metastasis and fibrosis [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%